Postgraduate radiology education in Nigeria: Looking backward and forward - Bukunmi M. Idowu (South African Journal of Radiology, 2018)
Formal postgraduate radiology education (residency training) in Nigeria commenced in 1976 at the University College Hospital, Ibadan, Oyo State. Currently, two postgraduate medical colleges (one national and the other international or regional) are saddled with the responsibility of superintending the training programme. This is a chronicle of the evolution of radiology in Nigeria with emphasis on the current status of the training programme and areas that require improvement. Though the programme has delivered a quality healthcare workforce for the country and the international community since inception, significant but surmountable difficulties still exist. It is hoped that all stakeholders and policy-makers will take note and safeguard the future of the specialty.